Effectiveness of caregiver-provided cognitive interventions on cognition, social functioning and quality of life among older adults with major neurocognitive disorder: a systematic review protocol. (November 2016) - Silva, Rosa; Cardoso, Daniela; Abrunheiro, Sérgio; Almeida, Maria; Apóstolo, João
Abstract : Review question/objective: The objective of this systematic review is to synthesize the best available evidence on the effectiveness of individual cognitive interventions (CIs) provided by caregivers on cognition, social functioning and quality of life among older adults (≥65 years) with major neurocognitive disorder (NCD). The review questions are as follows: What is the best available evidence on the effectiveness of individual CIs provided by caregivers on cognitive domains such as memory, problem-solving and verbal fluency among older adults (≥65 years) with major NCD? What is the best available evidence regarding the effectiveness of individual CIs provided by caregivers on the social functioning and quality of life among older adults (≥65 years) with major NCD?